الاستخدام المشترك لتكنولوجيا المعلومات وإدارة المعرفة لتحقيق قيمة عالية لأعمال البنوك التجارية الأردنية( ) - العلي عبد الستار محمد; العمري غسان عيسى (Journal of Economics and Administrative Sciences, 2008)
The problem of the study represented in the gap between what banks possess of Information Technology and Knowledge Management and what they need to help them in decision making and problem solving and achieving High Business Value. It formed a focus and fundamental point for this study in its analysis and interpretation. This was done by a scientific methodology and five chapters. The study aimed at analyzing the use of partnering Information Technology with Knowledge Management to achieve High Business Value at commercial banks in Jordan. Data were collected from 116 managers, experts, and advisors working for 16 Jordanian banks through a questionnaire designed as a tool to measure the model. The variables levels of the study were analyzed by using descriptive statistics (means, standard deviations, and coefficient variance). The relations were tested by inferential statistics such as Pearson’s correlation, and impact was tested by using simple and multiple regression linear. Then ANOVA Two-way analysis among more two groups, and on an interval dependent variable and one way ANOVA between two variable were used to test the differences. Through analysis of practical applications the study concluded a number of findings, the most important were: • The correlation’s investigation showed a strong and significant relation between Knowledge and High Business Value of banks business. The resulted correlation was (86.9%). Another strong relation coefficient was found between Information Technology and High Business Value (88.3%).There was also a very strong relation between the shared use of Knowledge Management and Information Technology and the High Business Value for the commercial banks (90.6%). • The test results on the impact showed a clear direct and positive impact in the obtained increment of the banks Business Value as a result of the combined use of Information Technology and Knowledge management reached 61.2% for Information Technology and 48.3% for Knowledge management. • The impact test results also showed a strong significant and direct impact in Business Value resulted from employment of Information Technology. The increase in one unit in one Information Technology variable affected the increase in High Business Value by (1.03) unit. On the other hand the increase in one unit in Knowledge Management affected the High Business Value by (1.26) rise.